The onset of large size in Cretaceous marine turtles (Protostegidae) evidenced by new fossil remains from the Valanginian of Colombia (2024)
The evolution of large size in vertebrates is a fascinating research topic, relevant, for example, for the Cretaceous turtles of the Protostegidae clade, which includes some of the largest turtles to have ever inhabited the Earth. However, there is still limited understanding regarding when and under what conditions large size emerged in this group. Here we describe several limb bones and fossil shell remains from the upper Valanginian, Rosa Blanca Formation of Colombia that, together, shed light on the onset conditions and characteristics of large-size evolution in protostegids. The material, although fragmentary, preserves enough features, such as the sigmoidal curvature of the shaft of the humeri in anterior view and their strong waist, to be attributed to Protostegidae. The fossil turtles described here constitute the largest ever known for the Early Cretaceous worldwide and the oldest record for their group. The ecological and climatic conditions of northern South America during the Late Valanginian are discussed as potential triggers of the emergence of large body size in protostegid turtles.